Cross-boundary human impacts compromise the Serengeti-Mara ecosystem - Veldhuis, Michiel P; Ritchie, Mark E; Ogutu, Joseph O; Morrison, Thomas A; Beale, Colin M; Estes, Anna B; Mwakilema, William; Ojwang, Gordon O; Parr, Catherine L; Probert, James; Wargute, Patrick W; Hopcraft, J Grant C; et al. (Science (American Association for the Advancement of Science), 2019)
Protected areas provide major benefits for humans in the form of ecosystem services, but landscape degradation by human activity at their edges may compromise their ecological functioning. Using multiple lines of evidence from 40 years of research in the Serengeti-Mara ecosystem, we find that such edge degradation has effectively "squeezed" wildlife into the core protected area and has altered the ecosystem's dynamics even within this 40,000-square-kilometer ecosystem. This spatial cascade reduced resilience in the core and was mediated by the movement of grazers, which reduced grass fuel and fires, weakened the capacity of soils to sequester nutrients and carbon, and decreased the responsiveness of primary production to rainfall. Similar effects in other protected ecosystems worldwide may require rethinking of natural resource management outside protected areas.